Analysis of the Boston Consulting Group (BCG) Matrix in Defending Market Share on Apple Brand Smartphones - Susi Lestari; Deliana; Nurlinda (Universitas Serambi Mekkah, 2024)
Abstract Apple Inc. is an innovative multinational company that has revolutionized and facilitated the development of personal electronics devices and the media industries, So it is necessary to research to analyze the position of Apple Incorporation to be able to compete with the other electronics companies by determining the market position of Apple Inc. in the BCG matrix (Boston Consulting Group) and formulating strategies to maintain market share. The research method uses descriptive analysis by describing the collected data as it is without intending to make general conclusions. The type of data in this study is secondary data obtained from the Global Smartphones Market Share report in 2022. Based on this result BCG Matrix owned by Apple Inc. shows that the company in 2022 is in the position of Cash Cows where the position has a low market growth with high market share. Thus the company can formulate strategies in the form of product development.